En studie om svenska börsnoterade fastighetsbolag : hur väl lämnas upplysningar om förvaltningsfastigheters värdering och varför kan detta skilja sig åt? - Englund, Erik; Eriksson Cordeschi, Emilio (SLU/Dept. of Economics, 2011)

(untitled)
Property companies’ results are affected by unrealized changes in value of properties. Since market values are never completely reliable there is always a risk with revaluation with property´s value. The fair value is determined only when a sale is completed. The paper studies how well the Swedish listed property companies reported under the accounting standard, IAS 40. That applies to investment properties with regard to the four qualitative characteristics understandability, comparability, reliability and relevance.